CITRA MEREK PREFERENSI DAN RELIGIUSITAS SERTA PENGARUHNYA TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH PEMBIAYAAN TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH PEMBIAYAAN (STUDI EMPIRIS PADA BMT-MASLAHAH CABANG KRUCIL) - Nuntupa, Nuntupa; Lailatul Hikmah, Selfia Dwi (universitas Islam Zainul Hasan Genggong, 2023)
The purpose of this study was to determine the effect of brand image, preference and religiosity on customer decisions in choosing financing at BMT Maslahah Krucil Branch. The research method used is a quantitative method. The population used is customers who do financing at BMT Maslahah Krucil Branch. The sample taken in this study were 86 respondents using simple random sampling technique. Data were collected using a questionnaire. Analysis of the data used is classical hypothesis testing and multiple linear regression with the help of SPSS 25 for windows. The results of this study indicate that brand image, preference and religiosity have a significant influence on customer decisions in choosing financing at BMT Maslahah Krucil Branch.